Penerapan Sanksi Hukum Tindak Pidana Pemerkosaan Yang Dilakukan Oleh Anak (Studi Putusan No. 65/Pid.Sus-Anak/2017/PN. Mdn) - Sharon Yudha Ginting; Anggreini Atmei Lubis; Rizkan Zulyadi (Universitas Medan Area, 2019)
Rape by some groups is grouped into acts of violence against women, even in some cases that often arise, rape can be committed by a man against his wife, children (nephew) or women who are at home with him, so that various terms of marital rape, sexual abuse appear, and incest, better known generally as acts of violence against women. The type of research used is normative juridical, namely the type of research conducted by studying existing norms or legislation related to the issues discussed. Application of criminal sanctions against children who commit rape in Decision No. 65 / Pid.Sus-Anak / 2017 / PN. Mdn with imprisonment for 3 (three) years and 6 (six) months. Also impose a crime on the child by undergoing Job Training for 1 (one) month at Upt. LKPS-Child and Youth Social Services (PSAR) of the North Sumatra Province Social Service in Tanjung Morawa. The factors that cause the occurrence of criminal acts of rape committed by children are due to social factors, and mass media factors, because the defendant is often in the internet cafe, so he can often watch pornographic films and practice them against his own girlfriend, the defendant wants to be responsible for his actions, but because there is no money and not approved by the family, the defendant is reported to the police to account for his actions.